(untitled) (Proceedings of the International Conference on Education, 2021)
: Generally speaking, students fail to understand many statistical concepts and are not able to use them for finding solutions to real problems. The goal of this work is to determine the impact of interactive simulations for the solution of statistical problems. The proposed method consists of four stages. During the first stage, students tackle several situations through experience and computer simulations. Then, the theory is stablished and some problems are worked out in class. During the last stage, a conceptual exam is solved by the students. Twenty eight students took part in the present work. The performance of students in this group was compared with the performance of students that belonged to a control group. The results illustrate that students were able to show a significant improvement in their performance through the strategy proposed in this work.